(2x-1)(2x+7)=0

Simple and best practice solution for (2x-1)(2x+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-1)(2x+7)=0 equation:


Simplifying
(2x + -1)(2x + 7) = 0

Reorder the terms:
(-1 + 2x)(2x + 7) = 0

Reorder the terms:
(-1 + 2x)(7 + 2x) = 0

Multiply (-1 + 2x) * (7 + 2x)
(-1(7 + 2x) + 2x * (7 + 2x)) = 0
((7 * -1 + 2x * -1) + 2x * (7 + 2x)) = 0
((-7 + -2x) + 2x * (7 + 2x)) = 0
(-7 + -2x + (7 * 2x + 2x * 2x)) = 0
(-7 + -2x + (14x + 4x2)) = 0

Combine like terms: -2x + 14x = 12x
(-7 + 12x + 4x2) = 0

Solving
-7 + 12x + 4x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-7 + -2x)(1 + -2x) = 0

Subproblem 1

Set the factor '(-7 + -2x)' equal to zero and attempt to solve: Simplifying -7 + -2x = 0 Solving -7 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -2x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -2x = 0 + 7 -2x = 0 + 7 Combine like terms: 0 + 7 = 7 -2x = 7 Divide each side by '-2'. x = -3.5 Simplifying x = -3.5

Subproblem 2

Set the factor '(1 + -2x)' equal to zero and attempt to solve: Simplifying 1 + -2x = 0 Solving 1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5

Solution

x = {-3.5, 0.5}

See similar equations:

| 3(p-13)+4=13 | | x^5-ax^2-ax+1=0 | | -6(8v-4)=6(6v+4) | | n+9=4v-6 | | 8y=3x-12 | | 2(1+8x)=4(4x+8) | | ax+y=bx+K | | -6(4x-6)=-18-6x | | (3i+8)(6i-7)= | | 4(x+5)-2x+2=3(2x-4)+x+9 | | x+90+70=180 | | -3(4v+8)=-18-6v | | H(t)=-16t^2+342+1000 | | 4/2x-2916=1/9 | | x^2+6x+12=2x-1 | | 30=-w+247 | | -7b+28=-8(5+3b) | | 4(32-2b)=144 | | 242-u=133 | | 1+7x=4x+16 | | 3(2x+5)=(3x+3) | | 5m+m-2m=20 | | 12n=7 | | 7p+2p+2p-p-2p=16 | | 16b-9b-b=18 | | y=-5t^2+20t+60 | | √2/2x-54=1/3 | | ln0.9/ln2= | | 17c+2c+2c-12c=9 | | 2t-2t+4t+t-3t=20 | | 7(2x+7)= | | 3p-2p+p= |

Equations solver categories